APPLYING SCIENCE LEARNING PHET SIMULATION TO IMPROVE PROCESS SKILL AND KNOWLEDGE ASPECT OF JUNIOR HIGH SCHOOL STUDENT - Sari, Dyah Puspita; Tjandrakirana, Tjandrakirana; Kuntjoro, Sunu (Universitas Negeri Surabaya, 2018)
This research aims to improve students scientific process and aspects of knowledge, as well as to know activity and the response of the students through the application of science learning assisted PhET Simulation Program to 30 students of eight grades in junior high school. This research was experimental research with one group pretest-posttest design. Data were analyzed by descriptive quantitative results: (a) Students science process skills are increase with an average value post test results of 80 (N-gain; 0.71 with high criteria); (b) Students aspects of knowledge are increase with an average value post test results of 80 (N-gain; 0.74 with high criteria); (c) Frequency of activities that do experiment/ observation that by 18.3 percent while activities that students do at least is behavior that is not relevant to KBM by 3%; (d) The students positive response to learning process (83% with very strong criteria). Conclusion of this research that application of science learning assisted PhET simulation program can improve students process skills and aspects of knowledge.